2021
DOI: 10.34056/aujef.852145
|View full text |Cite
|
Sign up to set email alerts
|

The Investigation of University Students Online Learning Readiness Levels

Abstract: ÖZ: Bu araştırmanın amacı; bir devlet ile bir vakıf üniversitesinde, meslek yüksekokulunda öğrenim gören öğrencilerin çevrimiçi öğrenmeye hazırbulunuşluk düzeylerinin incelenmesidir. Tarama modelinde desenlenen araştırmanın örneklemini 2020-2021 eğitim-öğretim yılı güz döneminde İngilizce I dersini alan birinci sınıf ön lisans öğrencileri (n=1392) oluşturmuştur. Araştırmanın verileri kişisel bilgi formu ile Demir (2015) tarafından geliştirilen ve altı boyuttan oluşan 'Üniversite Öğrencilerinin E-öğrenmeye Hazı… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In the field, the phenomenon of readiness is generally identified with students. It is possible to encounter this situation frequently in the studies in the literature (Açıkgül, 2019;Ersoy, 2019;Demir & Eren, 2021;Konak, 2021). Generally, school and lesson-subject readiness is emphasised.…”
Section: Discussionmentioning
confidence: 99%
“…In the field, the phenomenon of readiness is generally identified with students. It is possible to encounter this situation frequently in the studies in the literature (Açıkgül, 2019;Ersoy, 2019;Demir & Eren, 2021;Konak, 2021). Generally, school and lesson-subject readiness is emphasised.…”
Section: Discussionmentioning
confidence: 99%
“…This result is similar to those reported by Cakir and Horzum (2015) and Kuleli (2018). Yakin and Tinmaz (2013) and Gunbatar (2017) found that the online learning readiness of pre-service teachers was at a sufficient level, whereas it was found to be high by Demir Ozturk and Eren (2021).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…This development and convenience have had a positive effect on educational activities, as in many other fields, and have enabled the implementation of new teaching methods. Online learning within distance education, which offers education to the masses regardless of place or time, has developed into a significant teac hing method which is widely used with the developing technology (Cakir & Horzum, 2015;Demir Ozturk & Eren, 2021;Khurana, 2016;Saritas, 2013). Thus, using computers, phones, televisions and other electronic devices, teachers and students can carry out a similar teaching process to that which takes place in face-to-face education but at different times and in different places.…”
Section: Introductionmentioning
confidence: 99%